Do Zinc Supplements Reduce Mortality in Patients with COVID-19? A Systematic Review and Meta-Analysis - Abuhelwa, Ziad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.